Integrative transcriptomic and metabolomic analyses unveil tanshinone biosynthesis in Salvia miltiorrhiza root under N starvation stress - Lu, Li-Lan; Zhang, Yu-Xiu; Yang, Yan-Fang (PloS one, 2022)
Salvia miltiorrhiza is a model plant for Chinese herbal medicine with significant pharmacologic effects due to its tanshinone components. Our previous study indicated that nitrogen starvation stress increased its tanshinone content. However, the molecular mechanism of this low nitrogen-induced tanshinone biosynthesis is still unclear. Thus, this study aimed to elucidate the molecular mechanism of tanshinone biosynthesis in S . miltiorrhiza under different N conditions [N-free (N0), low-N (Nl), and full-N (Nf, as control) conditions] by using transcriptome and metabolome analyses. Our results showed 3,437 and 2,274 differentially expressed unigenes between N0 and Nf as well as Nl and Nf root samples, respectively. N starvation (N0 and Nl) promoted the expression of the genes involved in the MVA and MEP pathway of tanshinone and terpenoid backbone biosynthesis. Gene ontology and KEGG analyses revealed that terpenoid backbone biosynthesis, hormone signal transduction, and phenylpropanoid biosynthesis were promoted under N starvation conditions, whereas starch and sucrose metabolisms, nitrogen and phosphorus metabolisms, as well as membrane development were inhibited. Furthermore, metabolome analysis showed that metabolite compounds and biosynthesis of secondary metabolites were upregulated. This study provided a novel insight into the molecular mechanisms of tanshinone production in S . miltiorrhiza in response to nitrogen stress.